Analysis of ocean tide loading estimated from the gps coordinate time series: A case study for the belÉm, brasÍlia, eusÉbio, manaus and santa maria stations, Brazil - Marotta, Giuliano Sant’Anna; de Abreu, Mário Alexandre; de Matos, Ana Cristina Oliveira Cancoro; Monico, João Francisco Galera [UNESP]; de França, George Sand Leão Araújo (Sociedade Brasileira de Geofisica, 2019)
The Earth suffers deformations due to the gravitational attraction of the celestial bodies and the redistribution of water mass occurring by the action of the ocean tide. These effects are known as solid Earth tide (SET) and ocean tide loading (OTL), and can be estimated by observations of the amplitudes and phases of their tidal wave constituents. Considering hat Global Navigation Satellite System (GNSS) observations may be used to estimate these effects and that the solid Earth tide displacement is well resolved, this work estimated and analyzed the amplitudes and phases of the 11 principal constituents of ocean tide loading, using Global Positioning System (GPS) observations. The methodology was applied to data collected from five stations in Brazil, and the amplitudes and phases of the tidal constituents were estimated and evaluated regarding their values and convergence times. The results showed that most of the estimated parameters converged during the analyzed period. In addition, after correcting the effects of ocean tide loading in each GPS solution, using the computed parameters and the existing models, the coordinates were compared and the results presented some local differences, allowing to recommend the use of GPS to estimate tidal constituents considering the local behavior of the point.
Keywords: GNSS stations; OTL; Tidal constituents